Interactions between polysaccharides and gut microbiota: A metabolomic and microbial review. (October 2022) - Zhang, Dandan; Liu, Juan; Cheng, Hao; Wang, Hongliang; Tan, Yuzhu; Feng, Wuwen; Peng, Cheng
Graphical abstract: Highlights: Undigested polysaccharides modulate gut microbiota composition. Gut microbiota metabolizes polysaccharides into SCFAs by carbohydrate enzymes. Polysaccharides modulate gut microbiota metabolites such as BAs, Trp, TMA and LPS. Modulating effects on bacteria and metabolites are affected by chemical structure. Further studies are needed to screen key bacteria and metabolites. Abstract: In recent years, gut microbiota has become a hot topic because of its important role in health and diseases. Gut microbiota can produce a series of metabolites such as short chain fatty acids (SCFAs), secondary bile acids, tryptophan and indole derivatives. Over the past decade, a large number of studies have shown that oral polysaccharides can be transported to the colon and interact with gut microbiota. However, comprehensive summarization of the interactions between polysaccharides and gut microbiota is still lacking, especially from the perspective of other gut microbiota metabolites such as trimethylamine and tryptophan. In this review, we first summarized the comprehensive interactions between polysaccharides and gut microbiota, including (1) modulation of gut microbiota composition by polysaccharides, (2) gut microbiota metabolizes polysaccharides to SCFAs, and (3) polysaccharides modulate the production of gut microbiota metabolites including trimethylamine, tryptophan, lipopolysaccharides, etc. In addition, we also discussed the indirect effects of polysaccharides on intestinal barriers and gave our perspectives on future research on polysaccharides. This review not only helps explain the underlying mechanism of polysaccharides, but also provides a reasonable reference for the better utilization of polysaccharides.